Working time intervals and total work time on nursing positions in Poland - Danuta Kunecka (Nofer Institute of Occupational Medicine, 2015)
Background: For the last few years a topic of overwork on nursing posts has given rise to strong discussions. The author has set herself a goal of answering the question if it is a result of real overwork of this particular profession or rather commonly assumed frustration of this professional group. The aim of this paper is to conduct the analysis of working time on chosen nursing positions in relation to measures of time being used as intervals in the course of conducting standard professional activities during one working day. Material and Methods: Research material consisted of documentation of work time on chosen nursing workplaces, compiled between 2007-2012 within the framework of a nursing course at the Pomeranian Medical University in Szczecin. As a method of measurement a photograph of a working day has been used. Measurements were performed in institutions located in 6 voivodeships in Poland. Results: Results suggest that only 6.5% of total of surveyed representatives of nurse profession spends proper amount of time (meaning: a time set by the applicable standards) on work intervals during a working day. Conclusions: The scale of the phenomenon indicates excessive workload for nursing positions, which along with a longer period of time, longer working hours may cause decrease in efficiency of work and cause a drop in quality of provided services. Med Pr 2015;66,(2):165-172